On Elkies' method for bounding the transitivity degree of Galois groups. (January 2022) - Barth, Dominik; Wenz, Andreas
Abstract: In 2013 Elkies described a method for bounding the transitivity degree of Galois groups. Our goal is to give additional applications of this technique, in particular verifying that the monodromy group of the degree-276 cover defined over a degree-12 number field computed by Monien is isomorphic to the sporadic Conway group Co 3 .